MODERN UKRAINIAN OPERA: VARIETIES OF GENRES - SHCHITOVA, Svetlana; BRONDZIA MARTYNYUK, Valentyna (Studia Universitatis Babes-Bolyai Musica, 2023)
The article examines the state of modern Ukrainian opera of the 21st century, which reflects European and global trends aimed at updating the genre and searching for new genre models. The authors of the article purposefully chose works by composers of almost all age categories, which are quite different in terms of genre content – interpretation of traditions and innovation – from creative youth to the most famous artists in the whole world (E. Stankovich), and consciously focused attention on examples of modern opera from several regions of Ukraine: Kyiv, Kharkiv, Odessa, Lviv, Dnipro. This work, dedicated to modern Ukrainian opera, combined the efforts of a practicing composer and a musicologist-scientist. After all, the material of research in one of the sections of the article was the parody comic opera by Valentina Martynyuk (Brondzia), as an example of the only opera performance in the Dnieper region. The research methodology is based on historical-typological, genre-stylistic, comparative, and analytical methods. The historical -typological method is related to the problems of the opera genre at the modern stage, which needs updating and radical changes; genre-stylistic, comparative, and analytical methods allow us to draw conclusions about the peculiarities of genre models of modern Ukrainian operas. They reflect Ukrainian national traditions, including authentic music and modern compositional techniques. It is noted that the level of the ratio of traditional and innovative appeal to the opera genre is determined by the individual creative approach of a certain composer and director.